Plum pox virus infection level in Prunus species growing along roadsides or in backyards in Vojvodina province - Bagi, Ferenc; Barać, Goran; Iličić, Renata; Savić, Zagorka; Burmazović, Milan; Meszaros, Viktor; Popović, Tatjana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2021)
The present study was conducted on 106 leaf samples of Prunus species (44 plum, 47 myrobalan plum, 10 apricot, 3 peach, 1 blackthorn, and 1 sour cherry) collected from the Vojvodina province of Serbia and assessed for the presence of Plum pox virus (PPV) with the aim of establishing whether trees growing along roadsides and in backyards could be sources of PPV infection in commercial orchards. Analyses confirmed PPV infection in 68.2%, 38.6%, and 20% of plum, myrobalan plum and apricot samples, respectively. The infection level varied considerably across locations, with 80% noted in Uljma, followed by 69% in Sremska Kamenica, 60% in Bečej, 50% in Temerin, 50% in Senta, 40% in Petrovaradin, 31% in Novi Sad, 30% in Susek, and 20% in Subotica. As no difference in infection rates was noted between young and older plum trees, the infections seemed to have occurred in their early life stage. Trees growing along roadsides were infected to a higher extent (89.6%) than those in backyards (66.6%). In some cases, symptomless trees were also provento be PPV positive, indicating that they are a potentially important source of further virus infections. Due to the widespread presence of the virus, tolerant or hypersensitive cultivars are recommended for planting new orchards.
Keywords: plum pox virus; Prunus trees; virus infection; Vojvodina